(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Conservation-induced displacement is the process of removing local communities from their traditional homes and lands, for conservation purposes such as the creation of national parks and wildlife sanctuaries. This study highlights the complex impacts of conservation-induced displacement of the Barnawapara sanctuary and provides valuable insights for policymakers. The displaced families are provided agricultural land, irrigation facilities, infrastructure and compensation under rehabilitation. The present study highlights the changes that take place before and after rehabilitation on agricultural aspects of the rehabilitated group based on empirical research. In this research, primary facts have been collect through non-participatory observation, interview schedule, Focus Group Discussion and audio-visual recordings and secondary Data have been collected through related websites, research papers, government documents and books. After the displacement, there have been both positive and negative changes in the lifestyle and agricultural activities of the residents of Ramsagar village. Land ownership, implementation of schemes and mandi facilities have encouraged rural development but the growing problem of unirrigated land and decline in grain production needs to be addressed.